Analysis of Road Sight Distance and Support Facility: A Case of Jalan Babakan Anyar – Majalengka - Reci Tiana Reta; Andri Irfan Rifai; Mohamad Taufik; Joewono Prasetijo (Jurnal Syntax Transformation, 2024)
Road infrastructure is very important for the development of the economy and human mobility throughout the world. However, behind the importance of this extensive road network, a primary challenge continues to grow, namely the construction of safe and efficient road geometry. Due to the high population density in Indonesia, traffic jams and accident rates have increased. Serious accidents can occur if the road geometry is not suitable. This research has the main objective of carrying out planning regarding visibility distances and the condition of road facilities, such as existing lighting and traffic signs, to develop practical recommendations that can be implemented to increase traffic efficiency and safety at the Babakan Anyar - Kadipaten Highway location. The primary data collection method involves using official documents and reports following the guidelines in the Procedure for Geometric Planning of Inter-City Roads through the Director General of Highways in 1997. On the Babakan Anyar - Kadipaten Highway, which is included in the provincial road category and is a type of road arterie with flat terrain conditions, it has been decided to set a design speed of 100 km/hour for this research. Based on the 100 km/h design speed used in this research, the minimum stopping visibility required is 175 meters. However, because the planned value measured is 181.92 meters, the stopping visibility distance (Jh) is 181.92. Likewise, the minimum required visibility distance is 670 meters, but the value obtained is 751.89 meters, so a visibility distance (Jd) of 751.89 meters is used. In addition, lighting facilities are needed to increase visibility and reduce the risk of accidents by ensuring drivers can see the road, traffic signs, and obstacles.